Globalisation and governance: Contradictions of neo-liberal migration management - Henk Overbeek (Hamburg Institute of International Economics (HWWA), 2002)
Neo-liberal globalisation has primarily entailed the liberalisation of trade and capital flows, but largely ignored the issue of labour mobility. Most literature on the political economy of globalisation likewise ignores global labour mobility. This paper first asks how globalisation affects human mobility. The conclusion is that globalisation integrates the world population into the global labour market in three principal ways: through accelerated commodification of labour power, through the integration via transnational production of national and regional labour markets, and by various (sometimes new) forms of international labour mobility. Regulation of the global economy is increasingly informalised and privatised, argues the paper. This trend is also noticeable in the governance of migration flows. The emerging de facto international regime for the regulation of migration is at the same time restrictive (to curb undesirable forms of migration and strengthen state control) and liberal (to enhance the deregulation and liberalisation of the global economy). This emerging form of governance largely lacks democratic legitimacy. In the final section the paper argues that a new, democratic, multilateral regime for the regulation of migration flows must be set up which can reflect the interests not just of governments and transnational capital, but those of migrants and the populations at large as well. – – Neoliberale Globalisierung hat bisher die Liberalisierung von Handel und Kapitalflüsse impliziert, aber die Frage der Arbeitsmobilität weitgehend ignoriert. Die meiste Verhandlungen über die politische Ökonomie der Globalisierung haben ebenso die internationale Mobilität von Arbeit negiert. Dieses Arbeitspapier fängt an mit der Frage nach den Effekten von Globalisierung auf Mobilität von Personen. Die Schlussfolgerung ist dass Globalisierung die Weltbevölkerung in einen weltweiten Arbeitsmarkt integriert auf drei Weisen: durch beschleunigte commodification (?) der Arbeitskraft, durch Integration (über transnationale Produktion) von nationale und regionale Arbeitsmärkte, und durch verschiedene (manchmal neue) Formen internationaler Arbeitsmobilität. Regulierung der Weltwirtschaft wird zunehmend informell und privatisiert, und diesen Trend lässt sich auch bemerken bei der Regulierung von Migrationsflüsse. Das entstehende Regime für internationale Migration ist zugleich restriktiv (um unerwünschte Migrationsformen entgegen zu gehen und die Kontrolle des Staates zu stärken) und liberal (um die Deregulierung und Liberalisierung der Weltwirtschaft zu ergänzen). Dieses Regime entbehrt demokratische Legitimität. In den letzten Abschnitt wird argumentiert dass ein neues, demokratisches, multilaterales Regime für die Regulation von internationalen Migrationen errichtet werden soll, das sowohl die Interessen von Regierungen und Großunternehmen als auch die Interessen von Aus- und Einwanderer und betroffene Bevölkerungen repräsentieren kann.
Keywords: D30; P5; D63; 330; Globalisation; Global Governance; Migration; International Migration Policy; Multilateralism; Neoliberalism; Globalisierung; Internationale Arbeitsmobilität; Internationale Wanderung; Arbeitsmarkt; Marktintegration; Migrationspolitik; international; Wirtschaftsliberalismus; Welt